Econometric estimation of food demand elasticities from household surveys in Argentina, Bolivia and Paraguay - Lema, Daniel (2007)
This paper presents an econometric estimation of food demand elasticities for Argentina, Bolivia and Paraguay using household survey data. The empirical approach consists in the estimation of a censored corrected LinQuad incomplete demand system of eleven equations using microdata from national household surveys. The limited dependent variable problem is accounted for using the Shonkwiler and Yen two step estimation procedure. Comparative results suggest distinct consumption behaviors in Argentina, Bolivia and Paraguay. Food demand is in general less elastic in Argentina, particularly for dairy products, beef, chicken wheat and sugar. Estimated magnitudes of income elasticities shows a more elastic response in Argentina for dairy products, beef, chicken and oil.